The use of human teeth in identification: epidemiological data from an anthropology lab in Brazil - Raffaela Arrabaça Francisco; Maria Isabel de Oliveira e Britto Villalobos; Adrielly Garcia Ortiz; Maria Gabriela Haye Biazevic; Marco Aurelio Guimarães; Ricardo Henrique Alves da Silva (Bioscience Journal, 2016)
Forensic Odontology is a branch of Dentistry that works with the Law in assisting Justice and the professional involved in this specialty helping the identification of human remains, in various situations - charred corpses, cadavers and unidentified bodies. The aim of this paper was to list and analyze the number and types of teeth present in cadavers submitted to the Forensic Anthropology Lab of the Forensic Medicine Center (Ribeirão Preto), from 2005 to 2010, in order to evaluate and compare the importance of each dental element in human identification. During the research, the Lab received, inserted or submitted with the cadavers, for anthropological analysis, 588 teeth, of which 303 were upper teeth and 285 lower teeth. The upper teeth mostly found were the first and second molars (n=48) and the mostly found lower teeth were canines and first bicuspids (n=44). The most absent upper tooth ante mortemÂ was the third molar (n=25) and, on the lower arch, the first molar (n=33). In contrast, the most absent teethÂ post mortemÂ on the upper dental arch were central and lateral incisors (n=23 and n=20, respectively) and on the lower arch the same dental elements (central incisors - n=37, lateral incisors - n=28). The techniques for estimating age, ancestry, stature and gender by analysis of dental characteristics varied according to the population. In Brazil, due to the wide population miscegenation, the techniques mentioned may not present the same level of reliability, making it necessary to associate the dental exam to the anthropological analysis, in order to reach the most scientifically reliable results. It was concluded that, due to the importance of the dental elements in the process of human identification, it is necessary the presence of a dental surgeon in the team to collect the remains and perform the identification.